PROFIL METAKOGNISI MAHASISWA PEREMPUAN DALAM MENYELESAIKAN MASALAH BANGUN DATAR DITINJAU DARI GAYA KOGNITIF REFLEKTIF DAN IMPULSIF - Sugiyanti Sugiyanti; Rizky Esti Utami; Kristi Indriana (IKIP PGRI Bojonegoro, 2018)
Abstract: This qualitative study described the metacognition of female students with reflective and impulsive cognitive style in solving the problems of plane. The subjects of the study were female students of the fourth semester in Universitas PGRI Semarang period 2016/2017 whom was given the problems of plane. Data collection applies think aloud method. The analysis of data focused on students' metacognitive ability in three steps, i.e. planning, monitoring, and evaluating.This research showed that: 1) metacognitive ability of female mathematics students with impulsive cognitive style in solving the problem was not able to realize the thinking process, causing student has not been able to answer all the given problems with the correct results; and 2) metacognitive ability of female mathematics students with reflective cognitive style in solving the problem was able to realize the thinking process well in the planning, monitoring and evaluating stages, causing subject is able to answer all the given problems with the correct result.Keywords: Profile; Metacognition; Reflective; ImpulsiveAbstrak:Â Penelitian kualitatif ini mendeskripsikan metakognisi mahasiswa perempuan dengan gaya kognitif reflektif dan impulsif dalam menyelesaikan masalah bangun datar. Subjek penelitian adalah mahasiswa perempuan semester IV Universitas PGRI Semarang periode 2016/2017 yang diberikan soal pemecahan masalah bangun datar. Teknik pengumpulan data menggunakan metode Think Aloud Method. Analisis data difokuskan pada kemampuan metakognitif mahasiswa dalam tiga tahap yaitu perencanaan, pemantauan, dan pengevaluasian. Hasil penelitian menunjukkan bahwa: 1) kemampuan metakognitif mahasiswa matematika berjenis kelamin perempuan dengan gaya kognitif impulsif dalam pemecahan masalah belum mampu menyadari proses berpikirnya dengan baik, menyebabkan subjek belum mampu menjawab semua permasalahan yang diberikan dengan hasil akhir yang benar; dan 2) kemampuan metakognitif mahasiswa matematika berjenis kelamin perempuan dengan gaya kognitif reflektif dalam pemecahan masalah mampu menyadari proses berpikirnya dengan baik pada tiga tahap metakognitif menyebabkan subjek mampu menjawab semua permasalahan yang diberikan dengan hasil akhir yang benar.Kata kunci: Profil; Metakognisi; Reflektif; ImpulsifÂ